PENGARUH PENDEKATAN KETERAMPILAN PROSES TERHADAP HASIL PEMBELAJARAN SIMETRI SISWA KELAS V SEKOLAH DASAR - Maulisa, Yaumil; Hamdani, Hamdani; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the influence of the application of process skill approachment to the students learning outcome on symmetry material in grade V students of SDN 03 Pontianak Kota. The methodology  used is experimental method in the form of quasy experimental with noneequivalent control group design. The population of this study were all students of grade V sdn 03 Pontianak Kota. The  sample were decide by using random sampling technique that brought grade VB of 30 students as experimental class and grade VC of 32 students as countrl class. The data collection technique, whit test as data collecting rool. Based on the analysis it is found that tcount (2,040) > ttable (2,000) which means Ha is accepted. It is concluded that the application of process skill approachment has influence the students learning outcomes on symmetry material og grade V students of SDN 03 Pontianak Kota. Based on the measurement, the effect size is 0,52 which categorized as medium so it can be concluded that the application of process skill approachment gives medium influence to the students learning outcomes on symmetry material of grade V students of SDN 03 Pontianak Kota. Keywords:  Process Skill Approachment, Learning Outcomes, Symmetry